The Effect of Bacille Calmette-Guerin (BCG) on the Changes in Number and Functional Activities of Mononuclear Phagocytes in Malaria- infected Mice Model - Supargiyono -; Mahardika Agus Wijayanti; Tri Ratnaningsih; Dian Nugraheni (Pusat Kedokteran Tropis, 2011)
Introduction: Recent studies have indicated that Bacille Calmette-Guerin (BCG) vaccination may have benefi cial eff ect on the survival of infant living in malaria endemic area as well as of malaria-infected mice model. However, the impact of injection of BCG vaccine on the changes in number and functional activities of Mononuclear Phagocytes during malaria-infection in animal model is still poorly understood.Objectives: To evaluate the eff ect of BCG on the changes in number and functional activities of Mononuclear Phagocytes (MPs) during Plasmodium berghei infection.Methods: Two groups of 18 Swiss mice were used. The fi rst group was given 0.1 ml of BCG injection subcutaneously and the second was the control non-BCG group. One week after BCG injection, all mice in both groups were inoculated with 107 Plasmodium berghei infected erythrocytes. The parasitaemia were monitored daily and the number and functional activity of splenic and peritoneal macrophages were tested.Results: The parasites were detected in the blood of both groups on the fi rst day after infection. The parasitaemia in the control group grew slowly until day 3, followed by rapid increased up to 38.96% on day 9. Parasitemia of mouse which still alive on day 12 was 59.6%. The parasitaemia of BCG-injected mice were also increased at lower rate after day 3, and the mice still survive until day 15 after infection. The number of peritoneal macrophages from BCG-injected mice increased to a higher degree compared to the non-BCG injected mice. Moreover, the phagocytic activities of peritoneal macrophages in BCG injected group were increased higher up to twice (200%) of normal levels compared to the non-BCG control group which increase only up to 1,5 times (150%) of the normal levels.Conclusion: The injection of BCG on Plasmodium berghei infected Swiss mice resulted in the extension of survival of the mice until day 15, accompanied by higher increased in number of circulating blood, splenic and peritoneal MPs, and the phagocytic activities of peritoneal MPs up to 137% of the increased in non-BCG mice.Keywords: BCG vaccine, malaria, Plasmodium berghei, macrophages, phagocytosis.